Analisis Kemandirian Belajar Siswa dalam Pembelajaran Tematik di Kelas V Sekolah Dasar Negeri Rantau Sialang - Oktalia Susanti; Elpri Darta Putra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to describe student learning independence in thematic learning in class V SDN Rantau Sialang, Kuantan Mudik District, Kuantan Singingi Regency. This type of research is descriptive qualitative research. The subjects of this study were the fifth grade teachers and the rest of the fifth graders. The data collection techniques used were interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results showed that the fifth grade students already had independent learning in thematic learning. This can be seen from the activities while students study thematically. Students' independent learning attitudes that arise during thematic learning are 1) confident, 2) active in learning, 3) disciplined in learning and the last is 4) responsibility in learning. The conclusion of this study is that the teacher has carried out the learning process in accordance with the 2013 curriculum, namely the thematic learning of the teacher can develop the learning independence of fifth grade students at SDN 018 Rantau Sialang, Kuantan Mudik District, Kuantan Singingi Regency.